Social Interaction of Down Syndrome Children Through Social Media in the Digital Era - Setyowati, Rini; Edy, Sarwo; Nugroho, Djoko (DPPM Universitas Pelita Bangsa, 2023)
This research discusses the social interactions of children with Down syndrome through social media in the digital era. Down syndrome is a genetic disorder that causes sufferers to have a low level of intelligence and distinctive physical abnormalities. The aim of this research is to find out how social interactions of children with Down syndrome occur through social media in the digital era. This research uses a qualitative approach with case studies. The methods used to collect data include observation, interviews, and documentation. Four stages of qualitative data analysis were carried out, namely data collection, data reduction, data presentation and the final step was drawing conclusions and verification. The population of this study were children with Down syndrome in Pacitan and Wonogiri Regency. The sample from this study was 10 children with Down syndrome and their parents. The results of this research show that children with Down syndrome can interact with other people more intensely with technology, namely through laptops and cellphones. Children with Down syndrome can send written messages via social media, namely WhatsApp, Facebook, and TikTok. This research provides new information because many previous studies only focused on studying the use of social media in normal children. In fact, children with Down syndrome also use social media as a means of interacting with other people. Further research needs to be done to determine the consequences of this interaction.